Research Education: Perspectives and subjective processes involved in educational research - Harm H. Tillema; Juan José Mena Marcos; Lily Orland Barak (Revista Electrónica Interuniversitaria de Formación del Profesorado)
Educational research acknowledges that researcher’s beliefs and training play a role in framing the outcomes of any study. Research not only consists of defining objectives and following certain methods (search) but also of making decisions over the steps taking during the inquiry process (research).Establishing a conceptual framework to guide actions on the subjective processes in research is then crucial to control them. With that purpose in mind we offer researchers and Teacher Educators a heuristic tool to be conscious on the risks that can be taken when immersed in research interpretative process. This instrument could be utilised in PhD programs, masters and research projects.